THE READINESS OF ELEMENTARY SCHOOL TEACHERS IN IMPLEMENTING THE INDEPENDENCE CURRICULUM - Widyawati, Nur; Mudiono, Alif; Arifin, Slamet (Universitas Islam Balitar, 2024)
ABSTRACT This study aims to describe (1) teachers' understanding of independent curriculum policies, (2) teachers' readiness in formulating learning objectives of the Pancasila profile, (3) teachers' readiness in implementing 21st century learning, and (4) teachers' readiness in identifying students' potentials. The research design uses surveys and needs analysis. The study population consisted of 40 elementary school teachers in cluster 4 of Nglegok District, covering 5 institutions. The sample is determined using a random technique. Data collection techniques used questionnaires and interviews with teachers and principals. The results showed that the teachers understood (1) the essence of the independent curriculum policy, (2) how to formulate learning objectives for Pancasila student profiles, (3) how to implement 21st century learning, (4) the concept of identifying various kinds of student potential. The recommendations from the results of this study are: teachers need reinforcement in understanding learning outcomes in the independent curriculum, how to develop learning paths and objectives, steps for preparing school operational curricula, and implementing projects to strengthen Pancasila student profiles. Keyword: Elementary School Teacher Readiness, Implementation of the Independent Curriculum